Fetomaternal outcome of rheumatic heart disease in pregnancy: an observational study - Prasad, Tulika; Gupta, Tripti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Rheumatic heart disease (RHD) remains a significant global health burden, particularly among pregnant women in regions with limited access to healthcare. Pregnancy exacerbates the risks associated with RHD due to increased cardiac demand, potentially leading to adverse fetomaternal outcomes. This study aims to investigate the fetomaternal outcomes associated with RHD during pregnancy. Specific objectives include assessing the maternal outcome of patients with rheumatic heart disease in pregnancy and investigating the fetal outcome. Methods: It was a retrospective observational study to assess the outcomes of pregnant women and neonatal outcomes. Results: The findings reveal a significant burden of adverse fetomaternal outcomes associated with RHD during pregnancy. Maternal complications, such as maternal mortality (4%), mean gestational age 39.17 years, valvular disorder and mode of delivery, and fetal complications, including preterm birth, low birth weight, intrauterine growth restriction, and neonatal mortality, were also elevated in this population. Conclusions: Moving forward, further research is essential to enhance our understanding and optimize care for pregnant women with RHD.